Once-daily tenofovir disoproxil fumarate in treatment-naive Taiwanese patients with chronic hepatitis B and minimally raised alanine aminotransferase (TORCH-B): a multicentre, double-blind, placebo-controlled, parallel-group, randomised trial. Issue 6 (June 2021) - Hsu, Yao-Chun; Chen, Chi-Yi; Chang, I-Wei; Chang, Chi-Yang; Wu, Chun-Ying; Lee, Teng-Yu; Wu, Ming-Shiang; Bair, Ming-Jong; Chen, Jyh-Jou; Chen, Chieh-Chang; Tseng, Cheng-Hao; Tai, Chi-Ming; et al.
Summary: Background: Antiviral therapy for patients with non-cirrhotic chronic hepatitis B and minimally raised alanine aminotransferase (ALT) is controversial. We aimed to investigate the efficacy and safety of tenofovir disoproxil fumarate in reducing the risk of disease progression in this patient population. Methods: TORCH-B is a multicentre, double-blind, placebo-controlled, parallel-group, randomised trial done at six teaching hospitals in Taiwan that enrolled patients with chronic hepatitis B. Eligible patients were aged 25–70 years and had substantial viraemia (viral DNA >2000 IU/mL) and minimally raised serum ALT concentrations more than one-fold but less than two-fold the upper limit of normal (ULN). Exclusion criteria included liver cirrhosis and previous antiviral treatment. Eligible participants were randomly assigned (1:1), stratified by site with a fixed block size of ten, to receive either 300 mg of oral tenofovir disoproxil fumarate or placebo once daily for 3 years. The participants, investigators, research coordinators, pathologists, laboratory personnel, and staff involved in patient care or assessment were masked to treatment assignment. 0·5 mg/day of oral entecavir was added to rescue acute hepatitis flare. The coprimary outcomes were change in necroinflammation severity on the Knodell scale and change in fibrosis stage on the Ishak scale and were evaluated in the modified intention-to-treat population, which comprised all patients with paired liver biopsies. Safety was evaluated in all patients who were randomly assigned. This trial is registered at ClinicalTrials.gov, NCT01522625, and is completed. Findings: From Jan 30, 2012, to Nov 10, 2015, 875 patients were screened and 160 were randomly assigned to receive either tenofovir disoproxil fumarate (n=79) or placebo (n=81). The coprimary outcomes were assessed in 146 patients (73 in each group). Liver fibrosis progressed (an increase of ≥1 stage) in 19 (26%, 95% CI 17–38) of 73 patients in the tenofovir disoproxil fumarate group and in 34 (47%, 35–59) of 73 patients in the placebo group (relative risk [RR] 0·56, 95% CI 0·35–0·88; p=0·013), whereas necroinflammation progressed (an increase of ≥2 points) in five (7%, 95% CI 2–15) patients in the tenofovir disoproxil fumarate group and in 12 (16%, 9–27) patients in the placebo group (RR 0·42, 95% CI 0·15–1·12; p=0·084). Two (3%) of 79 patients in the tenofovir disoproxil fumarate group and 13 (16%) of 81 patients in the placebo group had acute hepatitis flare requiring add-on entecavir (RR 0·16, 95% CI 0·04–0·68; p=0·013). The two groups were otherwise similar in occurrences of adverse events. No patients died. Interpretation: Tenofovir disoproxil fumarate reduces the risk of progression in liver fibrosis in patients with chronic hepatitis B and minimally raised ALT, but its effect on necroinflammation is non-significant. Funding: The Taiwan Ministry of Science and Technology, E-Da Hospital, the Taipei Institute of Pathology, Gilead Sciences.